ADVANCING CRIMINAL PROCEDURAL MEASURES TO COMBAT TRAFFICKING IN NEWBORNS: A GLOBAL PERSPECTIVE - Khojabaeva Nargiza Isakovna (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2023)
Trafficking in newborns remains a pressing global concern, demanding comprehensive legal and procedural frameworks for effective prevention and prosecution. This article examines the multifaceted dimensions of criminal procedural measures in combating newborn trafficking, integrating insights from scholars and international criminal procedure legislation to propose cohesive strategies. The proliferation of newborn trafficking necessitates robust criminal procedural measures. This article amalgamates the perspectives of experts in the field with an analysis of criminal procedure legislation from diverse foreign jurisdictions to delineate effective strategies in combating this appalling crime. The author presents practical conclusions and conclusions based on the results of the study.